Analysis the carrying capacity of high school educational facilities needs in Bandung Regency - El Hamdi, Berry; Setiawan, Iwan (Penerbit Universiti Kebangsaan Malaysia, 2023)
Bandung Regency is the district with the largest population in Greater Bandung in 2021. The population is predicted to increase during Indonesia's golden momentum in the coming 2045. To prepare for this, an analysis is needed to see the carrying capacity of the current high school education needs facilities with a population in 2045. Data can be presented with WEBGIS. The aim of the research is to analyze high school educational facilities through capacity and capacity referring to Permendikbud No. 23 of 2016, and the carrying capacity of high school education facilities in 2045 refers to SNI 03-1733-20041, visualizing the required data through WEBGIS. The data uses residents aged 16-18 years obtained through the Sprague Multiplier method, and then uses the geometric projection method of the population to predict the population in 2045. The results of the study found that high schools in Bandung Regency in 2022 had discrepancies between groups and classrooms. Thus, the occupancy capacity exceeds the existing capacity (inefficient, and quite efficient). In addition, the existing Senior High School cannot optimally accommodate residents aged 16-18 years. For the carrying capacity of Senior High School needs in 2045, comment on the addition of 4 educational facilities (schools) for Cileunyi, Kutawaringin, Ketapang and Rancabali.